Translation and Conversation In Truth and Method by Hans-Georg Gadamer (Existential Analysis: Journal of the Society for Existential Analysis, 2011)
How do we translate one language into another? Is there such a thing as a mechanical translation? Hans Georg Gadamer (1975) contends that there is no 'purely literal' translation, for we always read a text with our own pre-understanding based on personal, social or cultural experiences. Therefore translation is an interpretation. There is no universal meaning of a text. Highlighting the constitutive features of translation in Gadamer's Truth and Method (1975, 2004), this paper explores how we come to understand, in both translation and in conversation, and reflects how Gadamer's insights can help us to elucidate a process of understanding in the reciprocity of conversation.
Keywords: Tradition; practical knowledge; prejudices; application; translation; fusions of horizons